Filling the out of season gaps for lamb and hogget production: Diet and genetic influence on carcass yield, carcass composition and retail value of meat. (February 2019) - Ponnampalam, E.N.; Kerr, M.G.; Butler, K.L.; Cottrell, J.J.; Dunshea, F.R.; Jacobs, J.L.
Abstract: This study investigated the use of camelina forage and meal supplementation to a finishing diet on carcass traits, composition and retail value of lamb and hoggets. The metabolisable energy and crude protein concentrations of all 3 diets were 10–11 MJ/kg DM and 14–15% CP. Thirty maternal Composite wether lambs (28–38 kg) and 30 Merino wether hoggets (37–43 kg) were used in a 3 × 2 factorial experiment. Animals were slaughtered after 10 weeks of feeding with carcasses classified as 'Heavy lamb' or 'Heavy hogget' (>22 kg carcass weight). Carcass traits, composition, meat mineral concentrations and retail colour were measured. Camelina diets increased liveweight (P < 0.02) and carcass weight (P < 0.002) for both sheep types. Carcass weight (P < 0.005) and dressing % (P < 0.01) were lower for Merino hoggets than Composite lambs. Mineral concentration and retail colour stability of fresh meat were unaffected by diet, with 72 h retail colour considered acceptable for consumers.